Investigation of S100B gene as a risk factor for biopolar disorder and schizophrenia - Dağdan, Elif (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2012)
Calcium-binding protein S100B has been implicated in the pathology of bipolar affective disorder (BPAD) and schizophrenia (SZP). S100B protein levels are elevated in serum of patients with both disorders compared to controls. Previously, genetic association of a SNP in the promoter of S100B, rs3788266, was reported for a psychotic form of BPAD. The disease- associated G allele of rs3788266 disrupts a Trex/MEF3 consensus recognition, which is bound by Six-family transcription factors, suggesting that it could affect S100B expression.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin